Analysis Of The Relationship Between Medical Service, Satisfaction, And Motivation With Doctor Performance At Sekarwangi Hospital - Idrus, Indri Savitri; Thaha, Abdul Razak; Maududi, Abul A'la Al (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Introduction: Problems related to the dissatisfaction of specialist doctors, especially those who do not perform surgical procedures, in obtaining medical services is caused by the medical service distribution system that is implemented that does not accommodate and appreciate the performance of the specialist. This dissatisfaction has a very significant impact on the quality of services provided by expert doctors and general practitioners. The job satisfaction felt by a doctor is an important issue because there is a relationship between the services provided such as the continuity of services and the cost of health services Materials and Methods: Data were taken in May 2025 using a questionnaire as an instrument using modified likert scale measurements. The research model used is a structural equation model (SEM) with a partial least squares (PLS-SEM) approach, with a sample of all functional doctors at Sekarwangi Hospital. Results: A total of 66 functional doctors at Sekarwangi Hospital participated in this study. Medical Services had a significant direct influence on Satisfaction with a path coefficient of ? = 0.434, p < .001, and an effect size of f2 of 0.232 (medium category). In contrast, the effect of Medical Services on Motivation (? = 0.308, p = .289) and Performance (total ? = 0.051, p = .686) was not significant, although there were positive indirect effects of Medical Services on Performance (? = 0.199, p = .118), through mediation pathways involving Satisfaction or Motivation. The effect of satisfaction on performance showed a total effect that was close to marginally significant (? = 0.350, p = .058) with an effect size of f2 of 0.102 (small–medium category), although the direct effect (? = 0.334, p = .157) was not significant at the conventional level. The direct effect of Satisfaction on Motivation was also insignificant (? = 0.103, p = .670), with a very small effect size (f2 = 0.010). The direct relationship between Motivation and Performance was also not significant (? = 0.153, p = .607), with a small effect size (f2 = 0.023). Conclusion: Although physicians' perceptions of the Medical Services system have been shown to contribute significantly to job satisfaction, it is not strong enough to directly drive an increase in their motivation and performance.